Relevance of trade credit during the global financial crisis : evidence from Singapore - Ma, Thiri Aung (2010)
This paper studies Straits Times Index (STI) firms’ performance (stock returns) with regards to firms’ two most important financing methods -- trade credit and bank credit -- during the global financial crisis (GFC). In particular, it analyzes how firms performed using the 5-day-week frequency data from June 2008 to January 2009, marking out 27-October-2008 as the peak of the GFC. We find evidence that accounts payable (AP), when examined in isolation, boosts firms’ performance during the GFC but worsens the performance during good times. Also, the relatively higher accounts receivable (AR), compared to AP, boosts the firm’s performance during good times but worsens the performance during the GFC. Furthermore, the effect of the GFC on firms’ performance does not decrease gradually over our study period of 6 months. Lastly, we find that a firm’s size, as categorized by market value, number of employees and asset, does not affect its performance and its borrowing (AP) as well as lending (AR) patterns.